Stevia rebaudiana Bertoni as a sweet herbal medicine: traditional uses, potential applications, and future development - Wang, Lisha; Chang, Tianying; Zhu, Tonggang; Hu, Wenxin; Wang, Xiaodan; Dong, Chenxuan; Sun, Yu; Zhang, Tianpeng; Jiang, Yue; Zhao, Chunna; Cui, Yingzi; Guo, Jiajuan; et al. (Frontiers in Pharmacology, 2025)
Steviarebaudiana Bertoni (S. rebaudiana for short), native to the Amambay Mountains of South America, is a sweet tasting medicinal plant with a long history of use in traditional medical systems. With the increasing global interest in natural products, their ethnopharmacological value and therapeutic potential have received growing attention from researchers, physicians, patients, and consumers. This review aims to comprehensively assess the ethnobotanical traits, traditional uses, pharmacological activities, major constituents, mechanisms of action, and safety profiles of S. rebaudiana. A comprehensive literature search was conducted using English and Chinese databases—Web of Science, PubMed, Scopus, ScienceDirect, CNKI, Google Scholar, and Elsevier—covering publications up to March 2025, including the keywords “ethnobotany”, “geographical distribution”, “traditional medicine”, “bioactivity”, “phytochemistry”, “pharmacological activities” and “toxicity”. Its taxonomic identity was confirmed using the Medicinal Plant Names Services (MPNS) and Plants of the World Online (POWO). Additional ethnopharmacological monographs and reference works were consulted to supplement database coverage. These findings show that S. rebaudiana has been traditionally used to lower blood glucose levels, reduce inflammation, and promote digestion. Modern research has identified bioactive metabolites, such as diterpenes, flavonoids, and phenolic acids, which exhibit antioxidant, anti-inflammatory, neuroprotective, and hepatoprotective effects. These properties have therapeutic potential for the management of metabolic disorders, cardiovascular diseases, neurodegenerative conditions and liver dysfunction. Although generally recognized as safe, some studies have reported immunological and reproductive concerns under high-dose or prolonged exposure, underscoring the need for further toxicological and clinical evaluation. In conclusion, this review bridges traditional ethnomedical knowledge with modern pharmacological evidence, providing a foundation for future research and the potential clinical translation of S. rebaudiana in phytotherapy.